Compressive and flexural strength of concrete with 30% Crushed Concrete Waste Aggregates (CCWA) and 70% Natural Aggregates (NA) / Mohd Baihaqi Kamaruzzan - Kamaruzzan, Mohd Baihaqi (Faculty of Civil Engineering, 2012)
Technology in concrete has been developing in many ways to enhance the quality and properties of concrete. From this technology, a lot of concrete were produced and give some impact to the environment such as reduction of raw material, addition in concrete waste, the addition of a waste disposal area for concrete. One of the waste products from construction industry is cube concrete. Cubes concrete have a potential as a course aggregate in fresh concrete. Furthermore, in the future, the amounts of nature aggregate will deficits. This research was carrying out to review the material properties of concrete which the concrete was produced from the crushed concrete waste aggregate (30% of CCWA) and natural aggregate (70% of NA) and to determine the compressive and flexure strength of the concrete. There are two test have been done in order to get compressive strength and flexural strength, which is compression test and flexural test. From the result, at days of 28th we can see that the compressive strength of concrete which mix with 30% crushed concrete waste aggregate (CCWA) and 70% natural aggregate (NA) is lower compared to plain concrete or control concrete.